Female figurines from early Christian Egypt as an example of archaism - Jędraszek, Sławomir (Acta Archaeologica Lodziensia, 2022)
The present paper offers some suggestions as to the way in which female figurines produced during the Christian period (IV-VII ce) in Egypt should be interpreted. They seem to have been predominantly used as a votive object as talismans, in others words as amulets endowed with sacred meaning, as expressions of personal, individual piety through religious worship. Their symbolical form had its background in the tradition of Egyptian terracottas of the Hellenistic period, but more specifically in a type of nude female figurine attested from the early dynastic period through the early Roman period. For this point of view, we should note that the concept of female figurines from the Christian period of Egypt, can be regarded as an example of religious archaism, both in its func¬tion and form, traditionally used as instruments of communications and the receipt of blessing at local cult centres in the Christian period in Egypt, where they were used in the r ites as personal possessions.